Komunikasi Dalam Kepemimpinan Kristen - Hasudungan Sidabutar; Devi Rianti Sinaga; Horasman Perdemunta Munthe (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2022)
Communication in leadership is something that is very important and fundamental because communication is a means for leaders to convey ideas for progress and success. This article examines how liberating and transformative communication should be for Christian leadership. Christian leadership upholds Christian values ​​according to what is written in the Bible. The method used in this article is a descriptive qualitative method with a literature study approach. This approach is used to explore and describe the nature of communication and the nature of Christian leadership. From this, a conclusion will be drawn on how the nature of communication in Christian leadership is transformative and liberating. A Christian leader must have good communication skills because it is related to his duty to influence, guide, direct, encourage members to carry out certain activities in order to achieve the goals that have been set and achieve effectiveness in leadership, planning, controlling, and coordination. The results of the study indicate that there are three important things in the communication of a transformative and liberating Christian leader, namely humanistic communication, good-relationship communication and communication that does not self-glorify. The conclusion of the study is that Christian leader communication should bring motivation, not intimidation. It is this motivation that moves everyone to work so that the common goals that have been set can be achieved.